Optimalisasi Penerimaan Pajak BPHTB di Kabupaten Sikka: Analisis Implementasi dan Tantangan - Angela S. B. Mbiri; Imanuel Welem; Paulus Juru (Dharma Ekonomi, 2025)
Bea Perolehan Hk Atas Tanah dan Bangunan (BPHTB) is one of the main sources of Regional Original Income (PAD) which is managed by the Sikka Regency Regional Revenue Agency (Bapenda). This research aims to analyze the optimization of BPHTB acceptance. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The research results show that the optimization efforts carried out, such as collaboration with notaries/PPATs, the use of technology through the "V-TAX" application, as well as increasing data monitoring and validation, have had a positive impact on BPHTB revenues. However, the main challenges still lie in the low awareness of taxpayers, administrative obstacles, and fluctuations in reported transaction values. Therefore, the recommended strategy includes intensive education for the community, improving facilities and infrastructure, as well as strengthening coordination with related agencies to increase tax compliance and the effectiveness of BPHTB collection.